THE ROLE OF LAW IN REALIZING SOCIAL JUSTICE: PERSPECTIVE OF PHILOSOPHY OF SCIENCE - Wafiya; Nur Sulistyo Budi Ambarini (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study discussed the role of law as an instrument for realizing social justice in Indonesia through the perspective of philosophy of science. Law was not only understood as a set of formal norms but also as a means of social transformation grounded in ontological, epistemological, and axiological foundations. Using a normative juridical research method and a qualitative approach based on literature review, this research analyzed the contributions of various legal theories and theories of justice including Satjipto Rahardjo’s responsive law, John Rawls’ theory of distributive justice, H.L.A. Hart’s legal positivism, Amartya Sen’s development paradigm, and Alasdair MacIntyre’s ethics of justice in shaping a legal framework that was inclusive and responsive to complex social realities. The findings showed that law in Indonesia had the potential to become a catalyst for social change through redistributive policies, protection of vulnerable groups, and strengthening of community solidarity. The perspective of philosophy of science deepened the understanding of the relationship between law and social justice, particularly in explaining the nature of law as an adaptive institution (ontology), the process of legal knowledge formation (epistemology), and the substantive values of justice underpinning legal practice (axiology).